Two Decades of Community-Based Marine Conservation Provide the Foundations for Future Action - Villaseñor-Derbez, Juan Carlos; Amador-Castro, Imelda G.; Hernández-Velasco, Arturo; Torre, Jorge; Fulton, Stuart (Frontiers in Marine Science, 2022)
As a member of the “High Level Panel for a Sustainable Ocean Economy”, Mexico has committed to expand community-based marine conservation. We draw from more than two decades of experience to outline how existing resources may be leveraged to help inform the country’s ambitious conservation plans. A total of 514.12 km2 have already been protected under community-based marine reserves. 14 years of ecological survey data, more than 130 community surveyors, more than one hundred publications, and an entire digital infrastructure provide a solid platform on which to continue building the community-based marine conservation movement. Parallel and complimentary efforts have advanced regulation, action, data access and transparency, and coordination. Future interventions should innovate, but leverage existing resources and continue to involve communities.